Preliminary results of productive and reproductive behavior of water buffaloes (Bubalus bubalis) in Cuba - Fraga, Luis M.; de Amorim Ramos, Alcides [UNESP]; Méndez, Mildred; García, Yenny; Gutiérrez, Maritza; Guzmán, Gladys; Mora, Marta (My University, 2010)
The wáter buffalo (Bubalus bubalis) was introduced in Cuba as a solution, but it was only considered such in the 80's. Later it reached a constant and full-throttled development as a result of the species characteristics throughout almost 25 years. According to MINAG estimations, in 2007 the herd reached 59,908 buffaloes and it is expected that this number increases to 88,436 buffaloes in 2010. The results of this 6-year-study is connected to the adjustment proposal for the selection scheme concerning the criteria and methodology, in order to improve the elements that have already been established by the National genetic improvement program for this species that is little known in this country. It was gathered productive and reproductive information from different farms in the country from four provinces (Habana, Matanzas, Villa Clara and Granma). In each of these farms, it was created a computerized database with the primary collected data, then they were incorporated in the SAS (2002 version 9.0) from which new characters were generated and depurated. Results from the environmental effects that affected the weight at birth and at weaning of calves and it was shown that the effect of native herd, 5 farms in this experiment (partial r2 of 19-29%), caused differences in the weight at birth (from 36 to 38 kg), while the same effect on weaning weight influenced values fluctuating from 110 to 135 kg. The major variation cause for these measures was the year of birth (partial r2 from 61 to 66%) which influenced with variations between 35 and 39 kg for weight at birth and from 95 to 130 kg for the weight at weaning in this same farm. In other herds we found that the season and birth order may be important (44 and 54% respectively) to the weight at birth if there are no adjustments to the age at first birth of mothers. While the milk yield and reproduction were assessed, many environmental effects (year of birth, season of birth, offspring gender, number of births). Year of birth, and the number or cycle of latency had higher incidence (12-75%) in the explanation of the variability of different measures. The seasonal effects varied according to the herd, even though it has been observed a negative effect when calving occurred out of season. Latency curves were studied according to different mathematical models and it was found the best adjustment with the logarithmic square function. Annual changes in weight at birth and weight at weaning showed differences in management practices and feeding during this period that should be studied in order to make them more stable and create more efficient production methods.
Keywords: Births; Calving interval; Milk production; Weight at birth; Weight at weaning